Perspective on the Economic Evaluation of Deep Brain Stimulation - McIntosh, Emma S. (Frontiers in Integrative Neuroscience, 2011)
Parkinson's disease (PD) is an example of a disease area experiencing increasing use of deep brain stimulation (DBS) to treat symptoms. PD is a major cause of morbidity and has a substantial economic impact on the patients, their caregivers, the health service, and broader social and community services. The PDSURG Collaborators Group reported that DBS surgery for patients with advanced PD improves motor function and quality of life that medical therapy alone at 1 year but there are surgery related side effects in a minority (Williams et al., 2010). The aim of this paper however is to build upon the knowledge generated from evaluating DBS in PD and to provide a detailed perspective on the economic evaluation of DBS more generally with a view to providing a framework for informative design of DBS economic evaluations. This perspective will outline the key categories of resource use pertinent to DBS beyond the surgical scenario and into the broader aspects of follow-up care, adverse events, repeat procedures, social and community care, patient and carer costs, and will explore the importance of handling capital costs of DBS equipment appropriately as well as including costs occurring in the future. In addition, this perspective article will outline the importance of capturing broader aspects of “outcome” or benefits as compared to those traditional clinical measures used. The key message is the importance of employing a broad “perspective” on the measurement and valuation of costs and benefits as well as the importance of adopting the appropriate time horizon for evaluating the costs and benefits of DBS. In order to do this effectively it may be that alternative methods of economic evaluation in health care to the commonly used cost-effectiveness analysis may have to be used, such as cost-benefit analysis (McIntosh et al., 2010).